Long-term major adverse cardiovascular events and quality of life after coronary angiography in elderly patients with acute coronary syndrome. (1st November 2016) - Sigurjonsdottir, R.; Barywani, S.; Albertsson, P.; Fu, M.
Abstract: Background: Although the elderly comprise the majority of acute coronary syndrome (ACS) patients, limited data exist on major adverse cardiovascular events (MACEs) and quality of life (QoL). Objectives: To study MACEs and QoL prospectively in ACS patients > 70 years referred for coronary angiography. Methods: A prospective observational study that included ACS patients > 70 years undergoing coronary angiography. The outcomes were MACEs and QoL 3 years after inclusion. MACEs were defined as death, recurrent ACS, new-onset of heart failure and repeated revascularization by coronary artery bypass grafting (CABG) or percutaneous coronary intervention (PCI). A QoL questionnaire was completed by the patients along with a physical examination and a personal interview at the 3-year follow-up. Multivariate analysis was performed to identify the predictors for MACEs. Results: In total, 138 patients (mean age 78.8 ± 3.8 years) with ACS were included in the study. Mean follow-up was 1196 ± 296 days. In all, 42% of the patients had MACEs and 25% had post-ACS heart failure. The mortality rate was 11%. After adjusting for significant cardiovascular risk factors, the following factors were significantly associated with MACEs: Age, high-sensitive troponin T (hsTNT), use of diuretics and reduced left ventricular ejection fraction (LVEF). Furthermore, the QoL evaluated with SF-36 in survivors from ACS at the end of study was similar to the QoL in an age-matched healthy Swedish population. Conclusions: In this prospective study on elderly ACS patients MACEs still occurred in 42% of the cases (despite low mortality and good QoL), with post-ACS heart failure as the most important event.